2014
DOI: 10.1002/chp.21227
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of a Remedial Education Program for Doctors With Clinical Performance Deficits

Abstract: Seventy-five percent of doctors who entered remedial education were considered to be practicing at an acceptable standard at the end of remediation. This accords well with international data. A small number of doctors appear to be unresponsive to remediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 17 publications
(32 reference statements)
2
49
0
Order By: Relevance
“…Our participants’ propensity to conceptualise remediation as an educational process and part of the educational support continuum mirrors the emphasis seen in the literature and appears to be consistent across (at least Western) health care systems. For example, in the UK, where doctors are employees, the National Clinical Assessment Service framework suggests that remediation ‘should still be seen as part of an educational continuum for improving practice’.…”
Section: Discussionsupporting
confidence: 59%
“…Our participants’ propensity to conceptualise remediation as an educational process and part of the educational support continuum mirrors the emphasis seen in the literature and appears to be consistent across (at least Western) health care systems. For example, in the UK, where doctors are employees, the National Clinical Assessment Service framework suggests that remediation ‘should still be seen as part of an educational continuum for improving practice’.…”
Section: Discussionsupporting
confidence: 59%
“…Even though most studies reported outcomes on only SUD, it could be that other performance concerns were addressed in the programme too (though not reported in the study). Our reported categories of concerns show similarities to how regulatory authorities structure their work regarding performance concerns of professionals, which usually channel professionals in different management pathways for concerns related to health, competence and conduct 43. Since there is often an overlap of performance concerns, professionals might be part of more than one pathway.…”
Section: Discussionmentioning
confidence: 66%
“…Of poorly performing physicians that completed a remedial professional development programme, 30%–40% succeeded in improving their performance for record keeping, clinical investigation, diagnostic accuracy and treatment and follow-up 42. A New Zealand study found that 14 out of 19 doctors (73.7%) that entered the remediation programme were considered to be practising at an adequate level at the end of remediation 43. A Canadian study looking at reassessed physiotherapists found that of eight physiotherapists who had a suboptimal outcome at the first assessment and who required remediation, practice enhancement or reassessments, seven (87.5%) scored the best possible outcome at the second assessment and one (12.5%) completed with recommendations 44…”
Section: Resultsmentioning
confidence: 99%
“…The term “problem doctor” [33,34] and related terms [35,36,37] are used in two ways. Some articles restrictively define “problem doctors” as those with poor clinical skills [33], but in other papers definitions are broader, including physicians who commit sexual offenses, are impaired, are disruptive, or are less than competent.…”
Section: Who Are the Difficult Colleagues?mentioning
confidence: 99%
“…Some articles restrictively define “problem doctors” as those with poor clinical skills [33], but in other papers definitions are broader, including physicians who commit sexual offenses, are impaired, are disruptive, or are less than competent. There are no sound investigations on the prevalence of physicians exhibiting problematic behaviors.…”
Section: Who Are the Difficult Colleagues?mentioning
confidence: 99%